2014
DOI: 10.1007/s11095-014-1566-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Εvaluation of Αnticancer Αctivity in Cells of Novel Stoichiometric Pegylated Fullerene-Doxorubicin Conjugates

Abstract: Pegylated DOX-C60 conjugates (1:1) and (2:1) with well-defined structure were successfully synthesized and found to exhibit comparable, but with a delayed onset, antiproliferative activity with free DOX against MCF-7 cancer cells. The results obtained justify further investigation of the potential of these conjugates as anticancer nanomedicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…A coupling of Dox and C 60 for a passive targeting of cancer cells can be achieved by covalent linkage [1517, 23] or by noncovalent interactions [1822]. A complex of C 60 with two amide-linked Dox molecules showed the same cytotoxicity against human breast cancer MCF-7 cells as the free drug [16].…”
Section: Introductionmentioning
confidence: 99%
“…A coupling of Dox and C 60 for a passive targeting of cancer cells can be achieved by covalent linkage [1517, 23] or by noncovalent interactions [1822]. A complex of C 60 with two amide-linked Dox molecules showed the same cytotoxicity against human breast cancer MCF-7 cells as the free drug [16].…”
Section: Introductionmentioning
confidence: 99%
“…Fullerene–biomolecule conjugates exhibit a very high antineoplastic efficiency. For example, the chemical attachment of anticancer preparations such as Paclitaxel and Doxorubicin (Dox) to C 60 fullerene results in an improvement of these drugs’ pharmacokinetics and increases their therapeutic efficacy (Liu et al 2011 ; Magoulas et al 2015 ; Prylutska et al 2015 ). Previous investigations from our research group revealed that pristine C 60 fullerene possesses a potent anticancer activity per se (Prylutska et al 2011a , b ; Lynchak et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…116 Magoulas et al . 117 studied the properties of fullerene C 60 conjugated with one ( 48 ) and two ( 49 ) units of doxorubicin (DOX), a potent anticancer agent (Fig. 11).…”
Section: Anti Cancer Propertiesmentioning
confidence: 99%